Fabrication and characterization of carbon nanotube-reinforced polypropylene matrix composites - Hussein, Hanady (AUC Knowledge Fountain, 2012)
Carbon nanotube reinforced polymer composites have recently been the focus of numerous research efforts. With regards to mechanical behavior, the enhancements reported are much lower than the theoretical predictions. One of the main challenges being tackled is achieving a uniform dispersion. Solvent mixing has been used extensively. Concerns, however, arose that unevaported solvents could negatively affect the mechanical properties. In this thesis, solvent and dry mixing for dispersing MWNT powders within the polymer prior to fabrication by melt processing are compared. Various weight fractions of CNT are added and the effect on the mechanical, crystallization and flow properties of the resulting composites is investigated. In both cases, enhancements in yield strength compared to the neat polymer were observed. It was found that dry mixing produced composites with the highest yield strength at 0.5 wt % CNT, whereas solvent mixing produced a similar enhancement at CNT contents of 1 wt %. It is believed that this difference is primarily dependent on the dispersion of CNTs within the polymer matrix. On the other hand, ductility was much higher for solvent mixed samples compared to dry mixed ones. FESEM analysis showed the presence of clusters in large wt % CNT samples produced by dry mixing. All samples produced by solvent mixing were found to contain homogeneously distributed CNTs. In most cases, CNT pull-out was found to be the dominant failure mechanism and may explain the limited enhancement observed. Further mechanical characterization was done using nanoindentation. The hardness and indentation modulus were calculated and they appear to concur with the tension test results. The crystallinity of the polypropylene matrix was also investigated before and after the addition of the CNTs. It was found that adding the lowest CNT wt% led to an increase in the crystallization temperature. A gradual increase in the crystallization temperature occurred with the addition of higher CNT loadings. This indicated that the CNTs acted as nucleating agents for the polypropylene crystals. In the plastics industry the flow properties of the polymer is very important. Melt flow index measurements were used in this study to analyze this property. A decreasing trend in the melt flow index i.e. increasing viscosity was found for the solvent- mixed samples which have superior dispersion expected to contribute to decreasing the viscosity of the molten polymer. However, the effect of the addition of the CNTs overcame this and resulted in the increase of the viscosity. This occurrence could be due to the dispersion process of solvent mixing preceding the shear mixing stage. Another indication for the poor dispersion of CNT in the dry-mixed samples was that the decrease in the melt flow index of the produced samples is very limited if not negligible.